KUALITAS LABA PERUSAHAAN MANUFAKTUR DI INDONESIA - Amalia Puspita Wardhani; Rossje V Surya Putri; Susi Dwi Mulyani (Media Riset Akuntansi, Auditing & Informasi, 2020)
The purpose of this research is empirically to find out the influence of business strategy, family owned, political connection and growth on quality of earnings with corporate risk as the moderating. This research uses moderated regression analysis data. The sample,is a manufacturing sectors and listed on,the Indonesia Stock Exchange by sampling 98 companies from 2013-2017. Sample,determination was done by using,purposive sampling method. Based on the results of the hypothesis analysis can be concluded that business strategy, family owned, and growth have a positive,impact on quality of earnings and political connection have a negative,impact on quality of earnings. This research also founded that coporate risk have a weaken of bussiness strategy on earnigs of quality, and corporate risk have a weaken of family owned on quality of earnigs. While corporate risk have no impact of political connection to quality of earnigs and corporate risk have no impact of growth on quality of earnings.